Morphology of ventricular septal defect associated with coarctation of aorta. Issue 2 (August 1983) - Anderson, R H; Lenox, C C; Zuberbuhler, J R
Abstract : It is now well established that the morphology of the ventricular septal defect associated with interrupted aortic arch is such as to compromise blood flow to the ascending aorta. Though there is some evidence that a similar mechanism may be operative in coarctation with ventricular septal defect, we are unaware of any necropsy study of this hypothesis. We therefore studied 25 hearts from the Heart Museum of Children's Hospital of Pittsburgh with coarctation and ventricular septal defect. Four had a malalignment defect with left ventricular outflow tract obstruction such as is seen in cases with interruption. Twenty of the remaining cases had a particular form of perimembranous defect with aortic overriding. The defects were partially closed by tricuspid valve tissue, the left ventricular outflow tract being further narrowed by various anatomical lesions. In addition, mitral valve malformations were present in 14 cases. The anatomy of the group as a whole suggests a possible reduction of aortic blood flow during fetal development. The clinical implications of these findings remain to be evaluated.